Analisis Kerusakan Transformator Distribusi 250 kVA Merek UNINDO Menggunakan Pendekatan Multi-Parameter TTR, IR, dan Pemeriksaan Visual - Dimas Airlangga Nugraha; Linda Faridah (Fuse-teknik Elektro, 2026)
Distribution transformers play an important role in ensuring the continuity of electrical energy distribution, so an accurate diagnostic method is needed to detect damage. This study aims to analyze the condition of a 250 kVA UNINDO brand distribution transformer using a multi-parameter approach through Transformer Turns Ratio (TTR), Insulation Resistance (IR), and visual inspection tests. TTR testing was carried out at seven tap positions, while IR testing used a voltage of 5 kV. The results showed that phases A and B were still within the tolerance limit of ±1%, while phase C did not show a ratio reading indicating open winding. Very low insulation resistance values (0.02-0.05 MΩ) indicated significant insulation degradation. These findings were reinforced by visual inspections that showed physical damage and indications of overheating in the phase C winding. This study confirmed that the integration of TTR, IR, and visual inspection methods was able to improve the accuracy of transformer damage diagnosis and support condition-based maintenance decision making in the field.